2021
DOI: 10.1021/acs.orglett.1c03903
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Antiaromaticity in Structurally Related Expanded Porphyrin-like Macrocycles with Benzene Linkers

Abstract: Phenylene-linked cyclotrimer (3T) and cyclotetramer (4T) have been synthesized via Lewis acid-catalyzed selfcondensation of appropriate precursors. Structural and Density Functional Theory (DFT) studies reveal the disruption of annulenic conjugation in both 3T and 4T by linking phenylene rings prevented them from global antiaromaticity. The single crystal X-ray structure of 4T reveals all the nitrogens are pointing toward the macrocyclic core with near-planar and square-shaped geometry, thus in sharp contrast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Hydrogen on pyrrole nitrogen of the porphyrin core can be replaced by metal ions to form metal porphyrins, while the hydrogen ions in peripheral methylene can be replaced by phenyl, pyridyl, phenylhydroxy, benzenesulfonic acid, and other groups to form porphyrin derivatives . Porphyrin belongs to the π–π conjugated macrocyclic system, around which the delocalization phenomenon of surrounding electrons is obvious, and its molecule has strong rigidity and aromatic properties . The above characteristics are beneficial to the transfer and separation of photogenerated electrons.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrogen on pyrrole nitrogen of the porphyrin core can be replaced by metal ions to form metal porphyrins, while the hydrogen ions in peripheral methylene can be replaced by phenyl, pyridyl, phenylhydroxy, benzenesulfonic acid, and other groups to form porphyrin derivatives . Porphyrin belongs to the π–π conjugated macrocyclic system, around which the delocalization phenomenon of surrounding electrons is obvious, and its molecule has strong rigidity and aromatic properties . The above characteristics are beneficial to the transfer and separation of photogenerated electrons.…”
Section: Introductionmentioning
confidence: 99%
“…9 Porphyrin belongs to the π−π conjugated macrocyclic system, around which the delocalization phenomenon of surrounding electrons is obvious, and its molecule has strong rigidity and aromatic properties. 10 The above characteristics are beneficial to the transfer and separation of photogenerated electrons. The large planar π-conjugated structure of porphyrins has inherent properties, such as photon absorption, high thermal stability, efficient electron transfer, absorption in the ultraviolet−nearinfrared region, high fluorescence, and efficient lighting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lash's group [8,15,28] and Latos‐Grażyński's group [10,19,20,27,29–31] and others [20,21,23,32–35] have extensively investigated the phenylene containing porphyrinoids, discussed their aromatic characteristics and shown their ability to form organometallic complexes by involving phenylene “C” along with pyrrole “N”s in coordination. Although the aromatic nature of m / p ‐phenylene containing porphyrins have been studied to greater extent but the aromaticity was not investigated thoroughly with m / p ‐phenylene containing expanded porphyrinoids since the reports on m / p ‐phenylene containing expanded porphyrins are relatively very few [20,33,36–39] . We recently reported the synthesis of [24π] dithia meta ‐benzisapphyrins 1 and [22π] dithia para ‐benzisapphyrins 2 and showed that the dithia p ‐benzisapphyrins 2 were aromatic whereas the dithia m ‐benzisapphyrins 1 were nonaromatic in nature [33] .…”
Section: Introductionmentioning
confidence: 99%
“…Although the aromatic nature of m/p-phenylene containing porphyrins have been studied to greater extent but the aromaticity was not investigated thoroughly with m/pphenylene containing expanded porphyrinoids since the reports on m/p-phenylene containing expanded porphyrins are relatively very few. [20,33,[36][37][38][39] We recently reported the synthesis of [24π] dithia meta-benzisapphyrins 1 and [22π] dithia parabenzisapphyrins 2 and showed that the dithia p-benzisapphyrins 2 were aromatic whereas the dithia m-benzisapphyrins 1 were nonaromatic in nature. [33] In continuation of our efforts in synthesizing more examples of expanded m/p-benziporphyrinoids to understand their structure, spectral and aromatic properties, herein we report our successful synthesis of nonaromatic [32π] m-benziheptaphyrins 3 a/3 b and aromatic [30π] p-benziheptaphyrins 4 a/4 b by adopting [5 + 2] condensation strategy using readily synthesized precursors.…”
Section: Introductionmentioning
confidence: 99%